Analysis of Marketing Strategies in Increasing Export Sales of Arabica Coffee at MDC Coffee House - Fikri, Adikha; Puspita , Desy (Journal Research of Social Science, Economics, and Management, 2025)
This study analyzes the marketing strategy implemented by MDC Coffee House to increase Arabica coffee export sales. Using a qualitative descriptive approach, the study identifies the strengths, weaknesses, opportunities, and threats facing the company through SWOT analysis, IFAS matrix, and EFAS. The results of the analysis show that MDC Coffee House has an IFAS value of 2.85 and an EFAS of 3.35, which indicates a strong internal position and a good response to external opportunities. Additionally, the GE Matrix indicates that the company is in the investment and development category, necessitating the implementation of an aggressive growth strategy. Recommended strategies include strengthening networks and transparency with suppliers, as well as diversifying products to meet diverse consumer demands. Furthermore, the study highlights the importance of leveraging technological advancements and regional economic developments to enhance competitiveness. By focusing on quality control and effective marketing communication, MDC Coffee House can further solidify its position in the global coffee market. This research is expected to provide valuable insights for academics, companies, and researchers regarding the importance of marketing strategies in increasing sales in the international market and fostering sustainable growth. The findings can also be a reference for similar enterprises aiming to enhance their export performance.